Advancements in the Treatment of Early-Stage Hemorrhoids - Poowaruttanawiwit, Prayuth (Journal of Basic and Applied Pharmacology, 2023)
Hemorrhoids are a prevalent condition affecting a significant portion of the global population. While early-stage hemorrhoids can be managed with relative ease, surgery may be necessary in certain cases. The advancement of early-stage hemorrhoid treatment has experienced substantial success in the past, particularly with the introduction of minimally invasive treatment methods and other innovative medical therapies. The aim of this review is to examine the progress made in both conventional and novel treatment approaches for hemorrhoids, and to propose potential avenues for future treatment development. Additionally, this review will highlight examples of new drug research and development techniques that hold promise for improving outcomes among patients with this condition.